Factors Militating Against Information Resources and Services Utilization by People Living With HIV/AIDS in Aminu Kano Teaching Hospital - Kabir, Muhammed Sani; Harande, Yahya Ibrahim (MiddleBelt Journal of Library and Information Science, 2020)
This paper investigates factors that militate against information resources, sources and services utilization by people living with HIV/AIDS attending Aminu Kano Teaching Hospital. Qualitative research method using cross-sectional survey design approach was used to collect data from the respondents. The population of the study comprises all the HIV/AIDS patients in AKTH, simple random sampling was used. Out of 10,025 patients 370 patients were selected to serve as respondents of the study. Factors identified are as follows: Insufficient health information, Unfavorable attitude of the officers concern toward the provision of the needed information, Difficulty of getting right information, lack of organized information resources, and problems of Internet connectivity. Recommendations made include providing sufficient health information, right information materials and organizing the acquired information resources in order to provide easy accessibility to the resources by the users. There is also the need to provide good and effective Internet services together with the creation of the site through which the PLWHA could get access to the available information resources and services provided by the hospital.